RESULTS OF THE USE OF HIGH-TECH TECHNIQUES IN THE COMPLEX TREATMENT OF VENOUS TROPHIC ULCERS OF THE LOWER EXTREMITIES IN ELDERLY PATIENTS - Ulug`bek R. Hamdamov (Central Asian Journal of Medicine, 2025)
To enhance the outcomes of intricate treatment for advanced stages of varicose veins in elderly patients. We examine the complex treatment outcomes of 15 elderly individuals with lower limb venous trophic ulcers (clinical class C6 according to CEAP) treated with stem endovenous laser ablation. The patients were 65±5 years old on average. Between the ages of 10 and 18, every patient had an open trophic leg ulcer. Using "Lakhta-Milon" laser equipment, endovenous laser ablation was carried out at a wavelength of 1470 nm. Prophylactic doses of low molecular weight heparins were recommended for five days following surgery in order to prevent venous thromboembolic consequences. The following day, a week, and a month following the procedure, the outcomes were assessed. the condition of the operated limb, the degree of obliteration of the venous trunk, and the local situation.